Employee Retention Strategy: Analysis Path Career, Compensation Benefit, Organization Commitment & Reward System - Azmieti Kurnia Sinta; Bekti Setiadi; Jumawan; Endah Suci Damayanti; Josua Panatap Soehaditama (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this literature review research is to see the correlation between the independent variable and the dependent variable, the novelty found is that there is a new framework in this study and previously there has been no constellation of problems like this research, the methodology uses a literature review study of various national and international journals, the results of this study are the significance between variables and the results of this study are the novelty of the framework model and new articles that have not previously been studied by other researchers. In the future, research can be developed with the variables in this scientific article with research methods, references, or objects used.